Productivity assessment and schedule compression index for construction project planning - Mansur, Shaiful Amri (2004)
Productivity assessment and performance evaluation models identified from previous researches were normally performed separately to reduce complication and cost. However, performing both the productivity assessment and performance evaluation would benefit a project progress significantly. Furthermore, effective schedule compression methods should be identified to maximise productivity and reduce additional costs. The aim of the research was to develop a project management tool that combined productivity assessment and schedule compression methods for reporting productivity status and evaluating project performance. The report is produced based on the level of Factors Affecting Productivity (FAP) and Schedule Compression Methods (SCM) obtained from the project. The research was divided into three stages, which involved a pilot, first round, and second round questionnaire surveys. The respondents of the surveys were mostly project and site managers from registered construction firms in several states of the Malaysia Peninsular. The first stage of the research involved identifying the importance and optimum level of project planning, differences between productivity and performance, fundamentals of productivity assessments, plus FAP and SCM from literature review. The pilot survey was used to determine the relevance, suitability and applicability of the information obtained from literature review to the local building construction industry using index of importance method. The second stage of the research involved two rounds of surveys. The objective of the first round survey was to obtain the minimum and maximum limit for FAP and SCM elements weighting process, and to develop the questionnaire for second round survey. The objective of the second round survey was to obtain historical data from completed building construction projects. A table of predicted time performance ratio (TPR) was produced using fuzzy inference system, which was to be used as a project performance index table. The results showed that FAP and SCM were positively correlated, and so were FAP and TPR. In conclusions, there was a need for effective and cheaper project management tools. Productivity assessment and SCM were implemented only by less than fifty percent of the survey respondents. Correct selection of construction methods, scheduling implementation, starting work as planned, complexity of construction and contractor’s budget allocation were considered as having high impact on FAP, while the most effective SCM claimed by the respondents was staffing the project with most efficient crew members. A status report that contained both productivity and performance status of a project was successfully produced.